P Penetapan Kadar Rhodamin B Pada Kerupuk Opak Bagula Di Kota Banjarmasin - Mawarid, Muhammad Taufiq Fawwaz; Aryzki, Saftia; Hidayah, Nur; Rahmadani, Rahmadani (LPPM Universitas Sari Mulia, 2024)
Background: Rhodamine B is a dye that is commonly used in the textile and paper industry, as a fabric dye, cosmetics, oral cleansing products and soap. This dangerous chemical is often misused in food production. This research aims to determine the chemical content in opak crackers which contain synthetic dyes such as rhodamine B circulating in the city of Banjarmasin using the HPLC method.Objective: This study aims to determine the presence and analyze the levels of rhodamine B in opak crackers circulating in the city of Banjarmasin.Methods: This research uses analytical observational research methods. Meanwhile, the design used in this research is cross sectionalResults: The results of qualitative analysis of injection of a standard solution of rhodamine B at a wavelength of 553 nm showed a retention time of 2.123 minutes. The results showed that samples (A), samples (B), samples (C) did not contain rhodamine B, characterized by different retention times. Meanwhile, the results of quantitative analysis using an HPLC instrument showed that no levels of rhodamine B were detected in all samples.Conclusion: Opak crackers circulating in the city of Banjarmasin, especially those sold at the pasar Ahad, Siring, and Taman Kamboja, can be declared safe or suitable for consumption